Is psychoanalysis based on the idea of the Kabbalah? - Chwalisz, Łukasz (Studia Psychologica: Theoria et praxis, 2007)
The article tries to establish a connection between the psychoanalysis and the cabbalistic thought. It presents the life of Sigmund Freud in the context of him being part of Jewish tradition and culture. It focuses on his family life, academic career and social environment. It briefly presents the history of the Kabbalah and describes its most important ideas like: Ein Sof, sefirot and The Tree of Life. Furthermore the article compares the psychoanalysis and the Kabbalah on the basis of occurrence in both such ideas and concepts as: unconsciousness, libido, symbolism and pan-sexuality. In the end it presents conclusions of the observations.